Natural gas dehydration using triethylene glycol (TEG) - Ahmad Syahrul, Mohamad (2009)
Dehydration of natural gas is the process removal of the water that is associated with natural gases. The objectives of this experiment is to remove water content in natural gas by using triethylene glycol (TEG).The mixtures of water in natural gas can cause the problems for the production operation, transportation, storage and use of the gas. The four major methods of dehydration are absorption, adsorption, gas permeation and refrigeration. The process of dehydration by using TEG is absorption, involves the use of a liquid desiccant to remove water content from the gas. This research focused on the effect of operating pressure and volumetric flowrate of natural gas. Before that, the engineering works was applied in order to make dehydration unit for the experimental of dehydration such as designing, fabricate and testing. From the result of experimental, the highest amount water content was removed when the operating pressure at lowest and the volumetric flowrate at highest. Higher amount of water content can be removed in the future study by carrying out the better dehydration unit.